Russian Arctic in the Contours of the Maritime Doctrine of the Russian Federation - Sergey Yu. Kozmenko; Arina S. Kozmenko (Арктика и Север, 2024)
During the decade of implementation of strategic planning in modern Russian reality, planning imperatives have also been introduced into the processes of geo-economic and political development of the Arctic, defining the system of goals and functional dominance of this geostrategic region, in particular, in medium-term perspective of budget policy implementation in 2024 and for the planning period of 2025 and 2026 [1]. During this period, Russia’s importance in the system of international relations increased, the country’s reputation and confidence in acquiring the status of a great maritime power, as well as in taking strong positions on land, as a state with centuries-old traditions of developing a large continental civilization, has been strengthened. At the same time, the role of the Arctic has noticeably increased, both among the regional directions of national maritime policy and in Russian foreign policy. Essentially, the Arctic began to determine the degree of state’s greatness at sea and in the world. This requires the comprehensive development of maritime potential. The main thing is to ensure, through the maritime potential, Russia’s guaranteed access to Arctic marine resources and space, including ensuring uninterrupted, preferably year-round, functioning of the national transport communication in the Arctic — the Northern Sea Route — the basis of the system of maritime communications. The Arctic nuclear icebreaker fleet and fleets of reinforced ice-class vessels are rightly considered the symbol of the Arctic maritime potential.